Priestly Aesthetics Disability and Bodily Difference in Leviticus 21 - Belser, Julia Watts 1978- (2019)
Leviticus 21:16-23 forbids priests with a wide range of disabilities from offering sacrifice at the altar, a ritual act that Leviticus considers the most sacred responsibility of the priesthood. This essay raises critical questions about the biblical writer's assumption that God desires the service of those with "perfect" bodies. The essay probes traditional Jewish interpretation of Leviticus 21 and argues that rabbinic texts leach the prohibition of much practical force. Despite offering a path toward more inclusive practice, conventional readings of these texts have left in place power dynamics that presume the inferiority of the disabled body. Yet they also contain the seeds for a conceptual shift that could transform the way contemporary communities engage with disability.Biblical Priests; Disability; Ethics; Jewish Theology; Leviticus 21; Rabbinic Literature; Talmud
Keywords: Bibel